SET activation of nitroarenes by 2-azaallyl anions as a straightforward access to 2,5-dihydro-1,2,4-oxadiazoles - Dong Zou (Nature Portfolio, 2021)
Oxadiazoles are five-membered ring heterocycles comprising an oxygen and two nitrogens, and those with the 1,2,4-oxadiazole skeleton are of interest due to their prevalence in biologically active compounds. Here, the authors report a transition metal-free [3+2]-cycloaddition of nitroarenes with 2-azaallyl anions under basic conditions to access 2,5-dihydro-1,2,4-oxadiazoles.